THE STATUS OF THE LAW OF PEACE IN COMPLETION OF DISPUTES OUTSIDE THE COURT - A Rahim; Abd. Rasid Pandei (International Peneliti Ekonomi, Sosial dan Teknologi, 2019)
This study aims to determine the legal strength of the peace agreement outside the court, the peace certificate accommodates the interests of the parties and the legal position of the peace certificate made outside the court. This research is a type of normative legal research. The approach used is the statutory approach. All research materials were analyzed using qualitative techniques. The results of this study conclude that dispute resolution outside the court will have permanent and binding legal force after the agreement is outlined in the form of a peace deed made by a notary public and is an authentic deed that is a deed that has perfect legal force. This means that if it turns out that one party is denying/defaulting, then the other party can ask for what has been promised. Then the peace deed made by the notary public has the force of executive law with the determination issued by the chairman of the District Court containing the request for execution so that the peace certificate can be implemented.